2021
DOI: 10.1136/bmjopen-2021-051316
|View full text |Cite
|
Sign up to set email alerts
|

Fitness, strength and severity of COVID-19: a prospective register study of 1 559 187 Swedish conscripts

Abstract: ObjectiveTo investigate the possible connection between cardiorespiratory fitness (CRF) and muscle strength in early adulthood and severity of COVID-19 later in life.DesignProspective registry-based cohort study.Participants1 559 187 Swedish men, undergoing military conscription between 1968 and 2005 at a mean age of 18.3 (SD 0.73) years.Main outcome measuresHospitalisation, intensive care or death due to COVID-19 from March to September 2020, in relation to CRF and muscle strength.ResultsHigh CRF in late adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 36 publications
0
50
0
3
Order By: Relevance
“…Despite the importance of an adequate physical fitness level, there is scarce evidence about its change during the pandemic, which is crucial, considering the role of physical condition in the severity of COVID-19 and other diseases [67,68]. Our research found that participants' perception of their physical fitness levels decreased in all groups, independent of the sex of parents and children's school type.…”
Section: Physical Fitnessmentioning
confidence: 54%
“…Despite the importance of an adequate physical fitness level, there is scarce evidence about its change during the pandemic, which is crucial, considering the role of physical condition in the severity of COVID-19 and other diseases [67,68]. Our research found that participants' perception of their physical fitness levels decreased in all groups, independent of the sex of parents and children's school type.…”
Section: Physical Fitnessmentioning
confidence: 54%
“…The value of these predictions will be explored further during the longitudinal cohort study, Military COVID-19 Observational Outcomes in a Viral Infectious Disease (M-COVID; Study No. 1061/MODREC/20) (37).…”
Section: Strength and Limitationsmentioning
confidence: 99%
“…Metabolic syndrome has been implicated in the attenuation of the immune response, with both obesity and diabetes independently affecting the structure, migration, and function of the cells, tissues, and other components of the immune system 8 . In addition to these conditions, physical activity reportedly protects against adverse outcomes in people with SARS‐CoV‐2, with prior cardiorespiratory fitness and strength conferring protection even many years later in people with SARS‐CoV‐2 infection, independent of other risk factors such as overweight 9,10 …”
Section: Figurementioning
confidence: 99%